Poverty and Subjective Poverty in Rural China - Hanjie Wang; Qiran Zhao; Yunli Bai; Linxiu Zhang; Xiaohua Yu (Social Indicators Research, 2020)
China is undergoing a campaign which is called “The Targeted Poverty Alleviation Policy” to eradicate extreme poverty from rural China until 2020. Though poverty in rural China has been studied intensively in different objective dimensions, little attention has been paid to poverty line settings and subjective poverty, which are hinged to the policy effects. In order to fill in the research gap, this study employs a nationally representative survey of rural households in 2016, to measure subjective poverty in rural China, and analyze the determinants as well. Our results indicate that the mean subjective poverty line of the rural households is 8297 yuan per capita, which is far higher than the national poverty line (2800 yuan). Statistically, 29% of the surveyed rural households who are not objectively poor feel subjectively poor. The objective poverty line cannot fully reflect the subjective poverty perception. Thus, how to reduce the subjective poverty perception could be a major policy agenda in rural China after 2020, when extreme poverty is no longer a problem.
Keywords: D63; I32; I38; 300; Rural China; Poverty lines; Subjective poverty; Objective poverty; The Targeted; Poverty alleviation policy